An enquiry into the information retrieval efficiency of LISA plus database - Sen, B.K. (1996)
Tests the information retrieval efficiency oj LISA Plus database in retrieving the abstracts oj articles on the library projession published in Asian library and information science journals jrom the ajorementioned database by employing two different methods oj computerised searches and a manual search. The manual search from LISA (printed version oj LISA Plus) retrieved 73 articles in 26 minutes, whereas the computerised searches retrieved 42 and 19 articles in 90 and 41 minutes respectively. Examines the reasons why computerized searches took more time and retrieved less number oj items. Suggests measures whereby the efficiency oj computerised searches can be increased and concludes that to ensure comprehensive recall of relevant items, a combination ojmanual and computerised search is indispensable.